2012
DOI: 10.1143/jjap.51.09mf07
|View full text |Cite
|
Sign up to set email alerts
|

Schottky Diodes Prepared with Ag, Au, or Pd Contacts on a MgZnO/ZnO Heterostructure

Abstract: We successfully fabricated lateral Schottky diodes with a thin MgZnO layer inserted between the ZnO and Schottky contact metal layers. The MgZnO/ZnO heterostructure was deposited onto a c-sapphire substrate by pulsed laser deposition using Mg0.3Zn0.7O and ZnO targets. Ti/Au was used to achieve ohmic contact with the Mg0.3Zn0.7O thin film layer, whereas Schottky contacts were prepared using silver (Ag), gold (Au), and palladium (Pd). The Ag Schottky diode devices exhibited rectification ratios as high as ∼103 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The Ag NPs not only enhances the UV response of the MgZnO detector at deep UV light but also greatly decreases the I dark noise level and increases the signal/noise ratio of the MgZnO detector, which has been reported to be mainly due to the localized Schottky junction at the interface between the Ag NPs and MgZnO thin film. 34 , 36 , 37 The barriers between the Ag NPs and MgZnO thin film are much thicker and the barriers are much higher at higher bias voltages under dark conditions, so the dark current of the MgZnO detector with 100 nm Ag NPs is much smaller than that of the detector without Ag NPs, 38 and the I uv / I dark ratio of the MgZnO detector with 100 nm Ag NPs at a 25 V bias voltage is much higher than that of the bared device.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Ag NPs not only enhances the UV response of the MgZnO detector at deep UV light but also greatly decreases the I dark noise level and increases the signal/noise ratio of the MgZnO detector, which has been reported to be mainly due to the localized Schottky junction at the interface between the Ag NPs and MgZnO thin film. 34 , 36 , 37 The barriers between the Ag NPs and MgZnO thin film are much thicker and the barriers are much higher at higher bias voltages under dark conditions, so the dark current of the MgZnO detector with 100 nm Ag NPs is much smaller than that of the detector without Ag NPs, 38 and the I uv / I dark ratio of the MgZnO detector with 100 nm Ag NPs at a 25 V bias voltage is much higher than that of the bared device.…”
Section: Results and Discussionmentioning
confidence: 99%
“…To find out if the Ag NPs induces much higher internal gain from hole trapping mechanism, the time response curves of the mixed-phase MgZnO-based detectors without and with 20–40 nm Ag NPs are measured, as shown in Figure 4 e,f. The rise time ( t r ) of the two MgZnO detectors are obtained through fitting of the photo response rise curves by adopting an exponential relation equation as shown in eq 3 , and the decay times ( t d1 , t d2 ) of the two MgZnO detectors are obtained through fitting of the photo response decay curves by adopting a biexponential relation equation, as shown in eq 4 ( 36 ) where y 0 is the steady-state photocurrent, t is the time, y 1 and y 2 are constants, t r is the rise time constant, and τ d1 and τ d2 are the relaxation time constants corresponding to two components (fast and slow). The rise time (t r ) of the bared MgZnO-based UV detector is 20 μs, and the two decay times (t d1 and t d2 ) of the device are 0.6 and 9.8 ms, respectively ( Figure 4 e).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Establishment of high‐quality Schottky contacts is necessary to achieve gate modulation in heterostructure field effect transistors (HFETs). However, only a few studies have been reported on Schottky contacts to MgZnO with, for example, a barrier height of 0.73 eV, an ideality factor of 2.37, and a rectification ratio of only 10 3 . Among various Schottky metals used for ZnO, Ag has been widely adopted because of its potential to create a relatively high Schottky barrier height (1.11 eV on bulk ZnO) with an ideality factor close to unity (1.08) .…”
Section: Electron Mobilities Sheet Carrier Concentrations Schottky mentioning
confidence: 99%